2015
DOI: 10.1093/pcp/pcv186
|View full text |Cite
|
Sign up to set email alerts
|

Staying Alive: Molecular Aspects of Seed Longevity

Abstract: Mature seeds are an ultimate physiological status that enables plants to endure extreme conditions such as high and low temperature, freezing and desiccation. Seed longevity, the period over which seed remains viable, is an important trait not only for plant adaptation to changing environments, but also, for example, for agriculture and conservation of biodiversity. Reduction of seed longevity is often associated with oxidation of cellular macromolecules such as nucleic acids, proteins and lipids. Seeds posses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
308
0
10

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(347 citation statements)
references
References 144 publications
2
308
0
10
Order By: Relevance
“…We cannot exclude that A9/A4a SUMOylation may also induce conformational changes that, as shown for HSF1 and CHIP1 (Kim et al, 2005), could contribute to the proposed recruitment. We showed that HSF SUMOylation is required for a transcriptional synergism that is involved in the enhancement of two crucial functions in seeds (Tejedor-Cano et al, 2014, and references therein): longevity and desiccation tolerance, both acquired in maturing zygotic embryos (reviewed by Dekkers et al, 2015; Sano et al, 2016; Leprince et al, 2017). Precedent studies in plants have only indicated functional connections of SUMOylation with non-embryonic development, for example with the control of flowering (Xu and Yang, 2013; Elrouby et al, 2013; Elrouby, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We cannot exclude that A9/A4a SUMOylation may also induce conformational changes that, as shown for HSF1 and CHIP1 (Kim et al, 2005), could contribute to the proposed recruitment. We showed that HSF SUMOylation is required for a transcriptional synergism that is involved in the enhancement of two crucial functions in seeds (Tejedor-Cano et al, 2014, and references therein): longevity and desiccation tolerance, both acquired in maturing zygotic embryos (reviewed by Dekkers et al, 2015; Sano et al, 2016; Leprince et al, 2017). Precedent studies in plants have only indicated functional connections of SUMOylation with non-embryonic development, for example with the control of flowering (Xu and Yang, 2013; Elrouby et al, 2013; Elrouby, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Seeds of Arabidopsis mutants that do not degrade Chl properly failed to germinate after 23 months of storage, whereas wildtype seeds maintained high germination rates after 42 months of storage (Nakajima et al, 2012). Phytyl tails released as a result of Chl breakdown are thought to serve as a substrate for the biosynthesis of tocopherols (well-known antioxidants involved in seed longevity; for review, see Sano et al, 2016). Craterostigma wilmsii plants in the dry state under simulated field conditions did not survive for more than 3 months, whereas 10 months of dry storage did not affect plant survival in X. humilis (Bajic, 2006).…”
Section: Regulated Shutdown Of Photosynthesis In Poikilochlorophylloumentioning
confidence: 99%
“…Although ROS may act as signaling molecules to regulate biological processes, they also damage cellular components and reduce longevity in the dry state Sano et al, 2016). Therefore, ROS levels must be tightly controlled in the cell via enzymatic and nonenzymatic ROS-scavenging systems Sano et al, 2016).…”
Section: Mechanisms For Longevity In the Dry Statementioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the mechanisms underlying seed viability and ensuring high quality of food protein need to be well understood. It is important to note that seed quality can be affected by prolonged storage (Sano et al, 2016), especially under high humidity and/or temperature conditions (Murthy, Kumar, and Sun, 2003;Walters, Ballesteros, and Vertucci, 2010;Sum, Sreenivasan, Singh, and Radhamani, 2013). Not less important are environmental conditions of seed development.…”
Section: Introductionmentioning
confidence: 99%